PENGARUH PERLAKUAN ALKALI, FRAKSI VOLUME SERAT, DAN PANJANG SERAT TERHADAP KEKUATAN TARIK KOMPOSIT SERAT SABUT KELAPA - POLYESTER - Pratama, Yudha Yoga; Setyanto, R. Hari; Priadythama, Ilham (Jurnal Ilmiah Teknik Industri, 2014)
Production of wood in Indonesia is no longer able to meet their need, which is opening an opportunity for study in material alternatives. Coconut fiber is very potential material for wood replacement composite, since its availability is abundant and its utilization is still low. Meanwhile, some factors have been studied as single affecting variable for natural fiber composite. The objective of this study is to evaluate the influence factors of alkali treatment, fiber length, fiber volume fraction and interaction between factors on the tensile strenght of coco-fiber polyester composite. 108 pieces of composites have been prepared as speciments of tensile test which comply ASTM D 638 standard. The testing result was processed usingÂ  completely randomized fullÂ  factorial experiment. The experiment showed significant difference for all three factors. The highest value of tensile strenght is 22.57 MPa for 2 hours alkali treatment, 10 mm fiber length and fiber volume fraction of 35%. This value has met the standard minimum tensile strength of hardboard according to ANSI A135.4 2004.